Design, Preparation, and Evaluation of Enteric Coating Formulation of HPMC and Eudragit L100 on Carboxylated Agarose Hydrogel by Using Drug Tartrazine. (28th January 2022) - Khan, Muhammad Junaid; Huang, Wen-Can; Akhlaq, Muhammad; Raza, Sajid; Hamadou, Alkassoumi Hassane; Yuning, Guo; Sun, Jianan; Mao, Xiangzhao
Abstract : Enteric-coated application on drug is used to prevent the drug from inactivation which are degraded by gastric enzyme. The present study is aimed at achieving controlled drug delivery in acidic medium of gastrointestinal tract (GIT) by enteric coating of hydroxy propyl methylcellulose (HPMC) and Eudragit L100 on carboxylated agarose hydrogel, creating a pH-dependent delivery system. Fourier-transformed infrared spectroscopy (FTIR) was for the detection of carboxylic group on agarose hydrogel, and scanning electron microscope (SEM) was used for the determination surface of prepared formulation. To check the pH sensitivity of enteric-coated formulation, different pH solution was used. It was found that the formulation was not dissolved in 1.2 but dissolve in pH 6.8 similarly; hydrogels lacking coating showed that tartrazine was more dissolved in pH 1.2, and less dissolved at pH 6.8. The release of tartrazine from the hydrogels was measured by using spectrophotometer and using a scanning electron microscope to examine the morphology and surface appearance of hydrogel capsules. This study revealed cracks on coated samples, while noncoated samples showed clear appearance with no cracks. Our findings revealed that this method could be useful for the development of an enteric coating drug delivery system.